Empirical analysis of natural farming in North-Eastern Hill region of India : a comparative study - Shivlal, Athawale Snehal; Ram Singh (Umiam : CPGS-AS, CAU, 2025)
The Green Revolution played a crucial role in alleviating food shortages in India., particularly benefitting large farms by enabling economies of scale. However, the intensification of agriculture in recent decades has often concealed enormous externalities, leading to adverse environmental aspects. This situation underscores the urgent need for substantial reforms in food systems, with agroecology, particularly 'Natural Farming' (NF) identified as a potential solution. NF is a unique chemical residual free farming method that is considered to be diversified farming system, which integrates crops, trees and livestock, allowing functional biodiversity. North Eastern Hill Region (NEHR) had a long history of practicing the traditional farming which aligns with the attributes of NF such zero/minimum tillage, intercropping, mulching, multiple cropping, crop rotation, no use of agrochemicals, integration of livestock, ITK's. However, there remains a lack of proper documentation and common terminology to designate it as 'natural farming' in the context of NEHR. Under this backdrop of the above context the following objectives have been formulated for the study - (1) To study
Includes bibliographical references.
Keywords: Natural farming -- North-Eastern Hill Region; Agroecology; Crop diversification